ANALISIS STRATEGI BAURAN PEMASARAN KRIPIK USUS RAMADHAN PADA MASA PANDEMI COVID-19 - Jamil, S. Hikmah; Rofiqoh, Ainur; Wildani, Melly (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2022)
The purpose of the study was to find out the marketing mix strategy carried out by theRamdhan intestine chips business during the covid-19 pandemic. The COVID-19 pandemic has had aprofound impact on various fields. Both health, politics, education, and economy. During the COVID-19pandemic, it has had an impact on small and large scale businesses. Many workers have been laid off orlaid off as a result of declining purchases by consumers. This research approach uses a qualitative descriptivemethod. From this research, it can be concluded that although the covid-19 pandemic also has an impact onthe Ramadhan intestine chips business, this business can still survive and even increase sales byimplementing a marketing mix strategy which consists of 4 marketing mix variables, namely product, price,promotion.Keywords: Marketing Mix Strategy, Product, Covid-19 Pandemic